1992
DOI: 10.1016/0014-5793(92)80248-f
|View full text |Cite
|
Sign up to set email alerts
|

NADH:ubiquinone oxidoreductase from bovine heart mitochondria A fourth nuclear encoded subunit with a homologue encoded in chloroplast genomes

Abstract: The amino acid sequence has been determined of the precursor ofa nuclear encoded 20 kDa subunit ofcomplex I from bovine heart mitochondria. The sequence of the mature protein is related to a protein of uncertain function, hitherto known as psbG, encoded in jhe chloroplast genomes of higher plants. Open reading frames encoding homologues of psbCi have also been detected in bacteria aud in the mitochondrial genomc of Purarn~ci~r~ retmurekt. The chloroplast p&G gcnc is found between n&C and n&J, which encode homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…5). Surprisingly this pattern is also found [14] in the PSST subunit of mitochondrial NADH:O oxidoreductase [15,66], except for the first Cys which is a Leu there. In 17 Ni-hydrogenases 6 additional conservative Cys residues are found in three more motifs (motifs 4S-6S; see Fig.…”
Section: The 'Small' or Fe-s Subunitmentioning
confidence: 72%
“…5). Surprisingly this pattern is also found [14] in the PSST subunit of mitochondrial NADH:O oxidoreductase [15,66], except for the first Cys which is a Leu there. In 17 Ni-hydrogenases 6 additional conservative Cys residues are found in three more motifs (motifs 4S-6S; see Fig.…”
Section: The 'Small' or Fe-s Subunitmentioning
confidence: 72%
“…The 49 kDa protein is homologous to NDH-H [32] and the 30 kDa protein to NDH-J [33,34]. Recently, Masui et al [35] have suggested that two more subunits belong to this fragment: a protein of 20 kDa (in the bovine enzyme) which is homologous to NDH-K [35,36] and the B13 protein [24,35]. Thus at least three, or if the 14 kDa polypeptide (B13 homologue) is included, maybe four polypeptides, are the same in the iron-protein fragment and our preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Steinmiiller;FAX: 49(211) homology to mammalian mitochondrial genes, which encode subunits of the NADH-ubiquinone-oxidoreductase (complex I) of the respiratory chain (Chomyn et al 1985(Chomyn et al , 1986. Recently, it was shown that four more reading frames of plastid DNA have homology to subunits of complex I and these were therefore designated as ndh genes: ndhH (Fearnley et al 1989), ndhI (WU et al 1989;Dupuis et al 1991), ndhJ (Videira et al 1990;Pilkington et al 1991) and ndhK (Berger et al 1991;Masui et al 1991 ;Arizmendi et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This view was questioned by the finding that the protein occurs predominantly in stroma thylakoids and it was suggested that it is an NDH subunit (Nixon et al 1989). Since a 20-kDa polypeptide with homology to NDH-K (PSII-G) has recently been identified in a complex-I preparation from bovine heart (Masui et al 1991;Arizmendi et al 1992), the classification as an NDH-protein is justified. The other subunit, the NDH-I protein (also designated as FRX-B, because of its ho-26 mology to ferredoxins), was originally found as a protein which binds to the replicative origin of chloroplast DNA (Wu et al 1989).…”
Section: Introductionmentioning
confidence: 99%